PEMETAAN TIGA DIMENSI (3D) LANSKAP CITYGML UNTUK SIMULASI ALIRAN ANGIN MENGGUNAKAN OPENFOAM - Zahra Izzaty, Ghalizha
In the perspective of a sustainable urban planning, wind flow is a fundamental and important factor to evaluate and must be taken into account in practically any urban planning processes. CityGML, with its urban and geometric concepts and their semantic relationships, can be useful for representing a wind flow analysis, as it could provide more precise and effective results when being integrated with a Computational Fluid Dynamics (CFD) software OpenFOAM to perform a wind flow simulation. This research demonstrates the process of urban wind flow simulation in ITB Jatinangor Campus with the use of CityGML LOD1 3D models. Point clouds obtained from a Digital Surface Model and 2D topographical map of ITB Jatinangor Campus are used for the creation of 3D city models. Wind flow simulation with LOD1 models results in a generally correct visualization of wind flow effects around buildings, except for the heights where the buildings’ roofs are supposed to be, as well as area with trees in it.